역특성가격함수를 이용한 승마장의 특성별 가치 추정 - 권오상 (한국농촌경제연구원, 2010)
An inverse hedonic function, suggested by Nerlove (1995), is estimated with a Korean riding club data set. Implicit prices for riding club's characteristics are derived from the estimated inverse hedonic function. A usual hedonic function for which quantity is assumed to be determined exogenously is also estimated, but is rejected by the inverse hedonic function by a nonnested hypothesis testing. Price elasticity of horse-back riding is estimated to be -0.67. It is shown that the WTP for riding is affected by riding club's location, accommodation, number of horses, trail length, number of instructors, parking lots and opening year.
Keywords: 체험 승마; 역특성가격함수; 경제적 가치평가; recreational equine; inverse hedonic price function; valuation